The Influence of Ludo Game Learning Media on the Learning Motivation of Fifth Grade Elementary School Students - Dya Ayu Agustiana Putri; Leny Suryaning Astutik; James Leonard Mwakapemba (Vocational: Journal of Educational Technology, 2026)
The research problem in this study concerns the low motivation of elementary school students in learning mathematics, particularly algebra, when taught using conventional methods. The purpose of this research was to examine the effectiveness of Ludo board learning media in enhancing students’ learning motivation of algebraic concepts. A quasi-experimental design with a pretest-posttest control group was employed, involving fifth-grade students divided into an experimental group and a control group. The experimental group received algebra instruction using Ludo board media, which integrated interactive elements such as dice rolls, token movements, and algebra-related questions, while the control group was taught through traditional instruction. Data on student motivation was collected using a validated 15-item questionnaire with high reliability (Cronbach’s Alpha=0.883). Pretest results indicated no significant difference between groups (p=0.548), confirming equivalence, while posttest analysis revealed a significant improvement in the experimental group compared to the control group (p < 0.001). The implications of these findings highlight that game-based learning media can increas the problem of low motivation by creating an engaging, interactive, and collaborative environment. The impact of this study demonstrates that integrating Ludo board media into mathematics instruction can accommodate diverse learning styles, foster social interaction, and improve motivation learning. This approach offers a practical strategy for enhancing the quality of mathematics education at the elementary level.